Evaluating radon loss from water during storage in standard PET, bio-based PET, and PLA bottles. (January 2016) - Lucchetti, Carlo; De Simone, Gabriele; Galli, Gianfranco; Tuccimei, Paola
Abstract: Polyethylene terephthalate (PET) and polylactic acid (PLA) bottles were tested to evaluate radon loss from water during 15 days of storage. PET bottles (lower surface/volume-ratio vials) lost 0.4–7.1% of initial radon, whereas PLA bottles lost 3.7% of it. PET bottles with volume of 0.5 L, lower surface/weight ratio, and hence higher thickness display proportionally reduced radon loss. Corrections for dissolved radium are needed during analyses. Formulas for calculating degassing efficiency and water interference on electrostatic collections are developed. Highlights: Radon loss from water during storage in polyethylene terephthalate (PET) and polylactic acid (PLA) bottles was evaluated. Surface/volume ratio and thickness of plastic materials were studied. A correction for dissolved radium concentration was applied to estimate gas loss. Proper corrections for degassing efficiency of aerators were developed. The interference of H2 O on radon daughter electrostatic collection was quantified.